Proceedings of the 2009 Winter Simulation Conference (WSC) 2009
DOI: 10.1109/wsc.2009.5429186
|View full text |Cite
|
Sign up to set email alerts
|

Three critical challenges for modeling and simulation in healthcare

Abstract: By most measures, the adoption of modeling and simulation techniques in healthcare service development falls well short of the uptake of such techniques evident in other sectors, such as business and commerce or aerospace and the military. The question is, why? To answer this, we consider three questions and then turn to the nature of answer which might lead towards greater adoption. The first is the vexed question of how good is good enough? The second concerns how best modeling should link through to decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…These benefits can easily be translated to other contexts such as services and healthcare. The actual implementation of DES in healthcare may not be so straightforward with authors positing a range of reasons why implementing DES in healthcare is more problematic than in other domains (Brailsford, 2005;Kuljis et al, 2007;Eldabi, 2009;Young et al, 2009). Two key differences that are stated in relation to the stakeholders are: the difficulty of engaging them in DES studies, and the problem of managing the conflicting interests of multiple stakeholders (Brailsford et al, 2009b;Eldabi, 2009).…”
Section: Defining Des and Its Key Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These benefits can easily be translated to other contexts such as services and healthcare. The actual implementation of DES in healthcare may not be so straightforward with authors positing a range of reasons why implementing DES in healthcare is more problematic than in other domains (Brailsford, 2005;Kuljis et al, 2007;Eldabi, 2009;Young et al, 2009). Two key differences that are stated in relation to the stakeholders are: the difficulty of engaging them in DES studies, and the problem of managing the conflicting interests of multiple stakeholders (Brailsford et al, 2009b;Eldabi, 2009).…”
Section: Defining Des and Its Key Assumptionsmentioning
confidence: 99%
“…As for manufacturing, simulation promises many benefits for health applications including risk reduction for changes to processes, cost and lead time reduction, increased customer satisfaction and greater understanding of healthcare processes among their stakeholders (Hollocks, 1992). However, these benefits are not necessarily being achieved with much evidence to suggest that simulation is simply not having the impact it could in the health sector (Young et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…patients, physicians, nurses) whose interactions do not result in the simple production of a final product, 'health'. Harper and Pitt (2004) and Brailsford et al (2009) discuss the complexity that arises from the interconnectivity of healthcare systems and Young et al (2009) point to the scale of healthcare systems as a source of complexity.…”
Section: Development Of the Questionnairementioning
confidence: 99%
“…This is driven by such factors as the increasing and aging population, especially in urban centres [29,30] with a knock-on effect for ambulance services. Comparisons with manufacturing and military usage have revealed a significant lack impact for healthcare modelling [31,32], and there has been a discussion of the barriers faced in healthcare [33,34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Young et al [34] have suggested the use of generic models as a strategy to improve the adoption of OR techniques in healthcare, enabling service managers to set up models or reuse them in analysing their specific systems. This work is consonant with earlier findings.…”
Section: Literature Reviewmentioning
confidence: 99%